2014
DOI: 10.1136/jnnp-2014-307591
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal inflammatory activity returns after natalizumab cessation in multiple sclerosis

Abstract: This study identifies rebound after NTZ cessation as an association of relapses and high MRI activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 10 publications
2
46
1
2
Order By: Relevance
“…Across 11 studies, 2 reported no evidence of rebound 123,135 and 1 reported no evidence of immune reconstitution inflammatory syndrome. 128 The proportion of participants showing evidence of rebound ranged, in most of the studies, from 9% to 12%, 126,127,131,132,137 whereas other authors reported higher rebounds, including 14%, 136 21.2% 134 and 38.3%. 138 Relapse outcomes.…”
Section: Review Questionmentioning
confidence: 98%
See 2 more Smart Citations
“…Across 11 studies, 2 reported no evidence of rebound 123,135 and 1 reported no evidence of immune reconstitution inflammatory syndrome. 128 The proportion of participants showing evidence of rebound ranged, in most of the studies, from 9% to 12%, 126,127,131,132,137 whereas other authors reported higher rebounds, including 14%, 136 21.2% 134 and 38.3%. 138 Relapse outcomes.…”
Section: Review Questionmentioning
confidence: 98%
“…After a full-text review and removal of duplicates, 19 studies met the eligibility criteria for this review. One study was an RCT; 120 12 were prospective cohort studies; [121][122][123][124][125][126][127][128][129][130][131][132] and six were retrospective cohorts. [133][134][135][136] In 15 studies, participants were receiving natalizumab before discontinuing treatment due to safety issues, whereas in one study, 127 participants were receiving fingolimod.…”
Section: Review Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stüve et al 17 reported on a small group of patients (n = 23) followed with immunologic, clinical, and MRI evaluations during 14 months after discontinuation of NZ that the effect of NZ decreased over a 3- to 6-month period. Similarly, a North American study 18 based on 175 patients with MS treated with NZ for at least 1 year showed that gadolinium-enhancing lesions were first detected 3 months after the last NZ infusion, and authors 19 reported in a small group of patients (n = 32) a reactivation of disease activity between 3 and 9 months after NZ interruption, independently of an alternative treatment prescribed.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the PML risk, natalizumab is often discontinued leading to MS disease reactivation [5] however, the ideal alternative treatment following natalizumab has not yet been identified [6][7][8]. Fingolimod (Gilenya, Novartis, Basel, Switzerland) is an option for these patients [1,3,[8][9][10][11][12] however, because of the still unknown impact on the immune system of the concomitant presence of these molecules, an interval is recommended between discontinuing natalizumab and starting fingolimod.…”
Section: Introductionmentioning
confidence: 99%